Mitochondrial genomes of Columbicola feather lice are highly fragmented, indicating repeated evolution of minicircle-type genomes in parasitic lice - Sweet, Andrew D.; Johnson, Kevin P.; Cameron, Stephen L. (PeerJ, 2020)
Most animals have a conserved mitochondrial genome structure composed of a single chromosome. However, some organisms have their mitochondrial genes separated on several smaller circular or linear chromosomes. Highly fragmented circular chromosomes (“minicircles”) are especially prevalent in parasitic lice (Insecta: Phthiraptera), with 16 species known to have between nine and 20 mitochondrial minicircles per genome. All of these species belong to the same clade (mammalian lice), suggesting a single origin of drastic fragmentation. Nevertheless, other work indicates a lesser degree of fragmentation (2–3 chromosomes/genome) is present in some avian feather lice (Ischnocera: Philopteridae). In this study, we tested for minicircles in four species of the feather louse genus Columbicola (Philopteridae). Using whole genome shotgun sequence data, we applied three different bioinformatic approaches for assembling the Columbicola mitochondrial genome. We further confirmed these approaches by assembling the mitochondrial genome of Pediculus humanus from shotgun sequencing reads, a species known to have minicircles. Columbicola spp. genomes are highly fragmented into 15–17 minicircles between ∼1,100 and ∼3,100 bp in length, with 1–4 genes per minicircle. Subsequent annotation of the minicircles indicated that tRNA arrangements of minicircles varied substantially between species. These mitochondrial minicircles for species of Columbicola represent the first feather lice (Philopteridae) for which minicircles have been found in a full mitochondrial genome assembly. Combined with recent phylogenetic studies of parasitic lice, our results provide strong evidence that highly fragmented mitochondrial genomes, which are otherwise rare across the Tree of Life, evolved multiple times within parasitic lice.
Keywords: Bioinformatics; Genome assembly; Convergent evolution; Phthiraptera